An International Perspective on The Protection of Freedom of Expression, with Special Emphasis on the Promotion of Racism, Xenophobia, and Religious Bigotry - Abdullah, Arez A.; Mahmod, Hoshman Ata; Salih, Hussein Mohammed; Ahmad, Hedayat Muhamad; Salih, Mihraban H. (Analisis: Jurnal Studi Keislaman, 2022)
The right to freedom of expression is a pillar of any democratic and pluralistic society. However, according to current international human rights standards, this right should be limited for several reasons, including others' rights and advocacy of national, racial, or religious hatred. In this study, the analytical method is adopted by analyzing the documents and the arguments made in the literature. Also, this is concerning some personal speech. Therefore, this paper has been divided into two parts; the first part deals with giving a comprehensive explanation and definition of freedom of expression through international and regional conventions. The second part begins with laying out the research's theoretical dimensions and looks at how this right should be limited for two reasons: regarding others' rights and advocating national, racial, and religious hatred. The main variables in this paper address various rights perspectives while considering current debates. This research concludes that freedom of speech, including press freedom, is a fundamental human right. Also, it is the job of the judicial branch and the rest of the legal system to protect human rights and freedoms.